Pembuatan Dan Karakterisasi Ekstrak Kering Herba Sambiloto (Andrographis Paniculata Nees.) - Harrizul Rivai; Gusmi Febrikesari; Humaira Fadhilah (Jurnal Farmasi Higea, 2014)
The research on preparation and characterization of dried leaves extract of simplicia sambiloto (Andrograpgis paniculata Nees.) has been done. The dry extract is made by adding various ratio of lactose, which is the ratio of the extract and drying with lactose 1x viscous extract (F1), 1½ x viscous extract (F2) and 2x viscous extract (F3). The name of the extract is Extractum Andrographis paniculata Nees. Siccum. The extract was in the form of dry powder, brownish green, tasteless with a very bitter taste. Levels of water soluble extract was 97,2472% ± 0,4598%, while levels of ethanol soluble extract 15,3012 ± 0,2594%.